"Filarial dance sign" real‐time ultrasound diagnosis of filarial oophoritis. Issue 8 (30th April 2016) - Panditi, Surekha; Shelke, Ashwini G.; Thummalakunta, Laxmi Narasimha Praveen
ABSTRACT: Filariasis is a parasitic disease caused by Filarial nematodes ( Wuchereria bancrofti, Brugia malayi, and Brugia timori ) that commonly causes lymphatic obstruction resulting in edema and increase in the size of the affected organ. Filariasis is diagnosed by identifying microfilariae on Giemsa stain. The immunochromatographic card test is diagnostic. Ultrasound is the imaging modality of choice for detecting adult filarial worms/microfilaria in the lymphatic system, which are responsible for the classic "filarial dance sign" caused by twirling movements of the microfilariae. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :500–501, 2016